Population structure and abundance of Sclerocarya birrea (A. Rich) Hochst subsp. birrea in two contrasting land-use systems in Benin - Gouwakinnou, Gérard; KINDOMIHOU, M. VALENTIN; ASSOGBADJO, ACHILLE EPHREM; SINSIN, Brice (My University, 2009)
The importance of indigenous fruit tree species for people living around protected areas is widely acknowledged. There is then a need to assess their conservation status in the current context of increasing human population and pressure around reserves. We investigated the population structure of Sclerocarya birrea, a multiple-use tree species in two land use systems in Northern Benin. Adult density was about nine times higher in the protected area (p < 0.001) compared to agroforestry systems (agro-systems). Seedling occurrence was similar in both land use type even though seed germination was best favoured in agro-systems. Saplings and adults with 5 - 20 cm dbh were almost absent in agrosystems. The mean diameter in agroforestry systems was about twice higher than in the protected area. Although a log-linear analysis showed a difference in the size class distributions between land use types (p < 0.0001), they were all positively skewed. Green’s index showed a clumped distribution in the protected area (0.48) compared to agro-systems (0.05). Population structure variation could mainly be explained by agricultural pressure. Saplings conservation is required in agro-systems to ensure sustainable use.
Keywords: Population structure; Sclerocarya birrea; land use; agroforestry systems; protected area